Immigrant perceptions of the police: the role of country of origin and length of settlement - Jung, Maria (The British journal of criminology, 2019)
Relationships between police and minority groups have been shown to be strained with members of these groups often viewing police in a more negative light. Distinguishing between minority group and immigrant populations, more recent work has shown that foreign-born individuals are more likely to view the police in a more favourable light than native-born populations. Adding to this literature, we examine group-specific factors that shape foreign-born individuals’ views of the police. We find that country of origin and length of settlement are important factors in better understanding immigrants’ perceptions of the police. The study concludes with a discussion of trust in police and recommendations for future research.